Prevalence and associated factors of metabolic syndrome among people living with HIV in a medical center of Northern Taiwan - Chien-An Tu; Chien-Feng Kuo; Chun-Ming Lee; Chang-Pan Liu; Hsiang-Kuang Tseng; Tseng-Yu Huang; Chih-Chen Lin; Hsun Chang; Winter Yu-Ning Lee; Fang-Ju Sun; Zu-Yi Sun; Pei-Ching Lian; et al. (Scientific Reports, 2025)
Abstract HIV acquisition has been found to be associated with increased risk of cardiometabolic syndrome in the past. In this study, we attempt to delineate the associated factors of metabolic syndrome among persons living with HIV in a single medical center in Taiwan using mostly integrase inhibitors-based regimen as HAART. A cross-sectional study involving all people living with HIV (PLWH) aged ≥ 18 years who visited MacKay Memorial Hospital, Taipei, Taiwan between September 7, 2022 to January 31, 2023 was performed. A modified National Cholesterol Education Program ATP III definition of metabolic syndrome was used to define metabolic syndrome and body mass index was used as surrogate for waist circumference. 809 PLWH participated in the study, in which 81.3% of patients were on integrase inhibitor-based HAART regimen. The prevalence of metabolic syndrome was 10.0%, which is markedly lower than those reported in the literature. Age was a significant risk factor for metabolic syndrome. HIV-related factors (CD4, viral load, HAART regimen) did not affect the presence of metabolic syndrome. Prevalence rate of metabolic syndrome appeared to have declined among PLWH compared to previous reports, possibly secondary to widespread use of integrase inhibitors. Age remains a strong risk factor for the development of metabolic syndrome among PLWH.